Impact of Situated Learning Approach on Teacher Learning: Physical Education Teacher Trainees' Perception of Disability and Inclusion - An, Jihoun (Social Education Research, 2022)
Globally, educational inclusion for Students with Disabilities (SWDs) has been a rising movement since the 1990s. However, discourses on professional development processes that prepare teachers to become inclusive practitioners for SWDs are still limited. This qualitative case study examined the learning experiences of Physical Education Teacher Trainees (PETTs) in an introductory adapted physical education course designed with a situated learning framework to explore its influence on their understanding of disability and inclusion in physical education. The course was re-designed incorporating three interrelated dimensions—context, learner, and activity—of situated learning. A qualitative intrinsic case study design driven by an interpretive perspective was undertaken to describe and understand the PETTs' experiences. Four PETTs (3 females, 1 male)' perceptions were gathered through a semi-structured interview, reflections on learning activities, photos, a pre-course survey, and field notes. Three themes emerged from the thematic analysis: (1) The power of authenticity in learning, (2) Beyond empathy: accepting individual differences, and (3) Inclusion as an integral part of education. Findings reveal that PETTs have shown perceptual transformation regarding disability and inclusion. This study discusses the PETTs' conceptualization of disability and inclusion with the notion that direct engagement with practices can deepen their learning within social and cultural contexts, such as adapted/inclusive physical education and social relationships with the Community of Practice (CoP).